The Politics of Post-Conflict Heritage Reconstruction
XVII, 258 p. 43 illus., 37 illus. in color.
Keywords: This edited volume explores the politics and semantics of heritage rehabilitation practices such as conservation, archaeological excavation, memorialization and rebuilding programs. Recent conflicts in the Arab region and Ukraine have demonstrated how heritage is an intrinsic part of contemporary warfare. However, the politicization of heritage reconstruction after conflict receives less attention. While there is consensus on the benefits of reconstruction, a growing number of scholars are now exploring the political agendas encoded in reconstruction programs, and their long-term negative effects on societal recovery. Faced with a contemporary heritage reconstruction wave in the Arab region, but also in (post-)conflict zones like West-Africa and Ukraine, it is important we are aware of the politicking encoded in many heritage aid programs. Through a series of co-authored studies by experts from different disciplines this book aims to identify parameters, practices and institutional organizations that either promote or undermine long-term societal resilience. By combining insights from archaeology, anthropology, conflict and history, this book will explore how heritage reconstructions help to re-shape national and ethno-religious identities and multi-layered memories of affected communities. Nour A. Munawar is an archaeologist and UNESCO heritage expert and currently works as a research fellow at the University of Amsterdam (UvA). He is the principal investigator of the “Decolonial Futures: Heritage, Memory, and Narratives in the Making in MENA” research project funded by the Dutch Research Council (NWO). He also works as a UNESCO Researcher for the UNESCO Documentary Heritage Unit on the “Documentary Heritage for Intercultural dialogue – a case study of AlUla, Saudi Arabia”. Gertjan Plets is an associate professor in Cultural History and Heritage at Utrecht University. At Utrecht he coordinates and conducts research in the field of heritage politics, theoretical archaeology, corporate sponsorship and Russian cultural politics. He broadly approaches cultural heritage as a cultural expression and political statement. His regional focus is Russia and the post-colonial Netherlands.